Evaluation of Antioxidant and Cytotoxic activities of Mycelia Biomass and Culture broth of three Edible Mushrooms, Morchella conica, Hericium erinaceus and Pleurotus florida Grown in Submerged Culture - Sneha Das; Frangleena P S; Kainoor Krishnankutty Janardhanan (International Journal of Fungi, 2024)
Mycelia biomass of three edible mushrooms namely, Morchella conica, Pleurotus florida and Hericium erinaceus were grown as submerged culture in potato dextrose broth supplemented with yeast extract, potassium dihydrogen orthophosphate and magnesium sulphate. The mycelia biomass was extracted with 70% ethanol and culture broth with ethyl acetate. The solvents were evaporated to dryness at low temperature using a rotary vacuum evaporator and the residues thus obtained were used for the studies.. The extracts of mycelia biomass and culture broth were evaluated for antioxidant, cytotoxic and antiproliferative activities. Antioxidant activity of extracts was assayed by DPPH (2,2-dyphenyl- 1- picrylhydozyl ) radical scavenging assay, FRAP (Ferric ion reducing antioxidant power), superoxide radical scavenging and lipid peroxidation inhibiting assays. Cytotoxicity of mycelia and culture broth extracts were assayed by MTT ( 3-(4,5-Dimethylthiazol-2-yl)-2-5 diphenyltetrazolium bromide ) assay using HepG2 liver cancer cell line and antiproliferative activity by using DLA (Dalton’s Lymphoma Ascites ) cell line. Among three mushrooms examined, ethanol extract of mycelia of M.conica and ethyl acetate extract of culture broth of H. erinaceus possessed highest antioxidant activity.The extracts of M. conica and H. erinaceus had a significant cytotoxic effect against DLA cells than P. florida.. Ethyl acetate extract of culture broth of H. erinaceus showed the highest cytotoxic activity against HepG2 liver cancer cell lines. The experimental results suggest the possible use of the mycelia and culture broth extracts of these mushrooms as supplements in cancer treatment. The findings also reveal the mycelia and culture broth of medicinal mushrooms have similar therapeutic potential as the fruiting bodies.
Keywords: Hericium erinaceus; Morchella conica; Pleurotus florida; culture broth; mycelia biomass